Analisis Dampak Pembebasan Lahan Tol Terhadap Ekonomi Masyarakat Terdampak Di Desa Alassumur Lor - Qomariyah, Nurul Ulfa; Fitriyah; Rizki Febri Eka Pradani (EKALAYA : Jurnal Ekonomi Akuntansi, 2024)
The land acquisition for the toll road in Alassumur Lor Village has significant impacts on the affacted community’s economy. This study analyzes the effect of toll land acquisition on the economic aspects of the impacted community in Alassumur Lor Village. The focus is on both the positive and negative impacts of toll land acquistion on the local economy, the responsible parties for the land acquistion, and the appropriate compensation costs. Through qualitative methods such as observation, Interviews, and documentation, it was found that despite an increase in income and expenditures, there are also negative impacts such as the loss of productive land and limited alternative employment opportunities. Understanding thes consequences, this research provide valuable insights for improving infrastructure development policies in the future.